Pertanggung Jawaban Direksi Atas Perbuatan Hukum Yang Terjadi Dalam Perseroan Terbatas Dilihat Dari Undang–Undang Nomor 40 Tahun 2007 - Albari Wira Satya (JOURNAL of LEGAL RESEARCH, 2022)
The duties and responsibilities of the Board of Directors according to the Company Law No. 40 of 2007 are that the Company's Directors are fully responsible for the management of the company for the benefit of the company and the company's objectives and are tasked with representing the company both inside and outside the court in accordance with the Articles of Association as stated in Article 1 paragraph (5) UUPT. The responsibility of the board of directors to the members of the board of directors, either individually or jointly and severally, if proven to have committed acts against the public is their full responsibility by taking ultravires actions (the actions of the directors are outside the aims and objectives as well as the company's business activities as specified in the Articles of Association)